Analyzing the multidimensional non-traditional security challenges in North Africa and regional implication - Bendebka, Ramzi (INTPOLSEC Publishing, 2025)
The non-traditional security challenges in North Africa have experienced significant changes in recent years. In addition to conventional military issues, the region has experienced many problems, such as drug trafficking, illegal immigration movements, smuggling, the Arab Spring, and the consequences of the global 'War on Terror' launched after the events of 9/11. Most research on North African security concentrates on threats within the traditional paradigms of military matters and terrorism. Nevertheless, this paper considers the overall parameters of an expanded North African regional non-traditional security. It focuses on four specific issues: illegal immigration movement, water scarcity, drug trafficking, and smuggling. The study indicates that if coordinated action is not taken, the interaction of these non-conventional risks can erode the future stability and growth of North Africa